Automated Model Synchronization: A Case Study on UML with Maude - Boronat, Artur; Meseguer, José (Electronic Communications of the EASST, 2011)
Design specifications of software-intensive systems involve models that have been defined with different modelling languages for different purposes. Hence, a specification can be seen as the description of a system from multiple viewpoints, each providing domain-specific constructs for modelling the system in a more precise way. Such heterogeneity of models can jeopardize the consistency of the specification, because updates in one viewpoint may cause unpredictable design errors in other viewpoints, which can then be transferred to the implementation. OMG’s Meta-Object Facility enhances the automation of the model consistency management by providing a uniform format for different modelling languages. In this paper, we illustrate a technique, based on rewriting logic and on strategies for finding inconsistencies in MOF-based heterogeneous specifications and for resolving them in an automated way.